Do Serviço Social no Brasil e da questão socioambiental do século XXI: uma abordagem à ecologia de Marx - Vieira, Sergio Luiz de Souza (2017)
The humanity experiences new moments of uncertainty. We came to the 21st century of the Christian was in the midst of the astonishment of the finite support of life on the planet, due to the affectations in the biosphere. Given this dramatic context, the UN - United Nations has made constant calls for all social segments to reflect on their environmental responsibilities. In this sense, this thesis seeks to provide new reflections on the historical sense of Social Work in contemporary times and seeks to draw attention to the socio-environmental aspects that are articulated with the legal attributions of the profession in Brazil. Part of the realization that the social misery and social question identified in the 19 st century by Karl Marx and Friedrich Engels were in fact disputes over the different uses of natural resources, therefore, it is shown that they were expressions of the socio-environmental question. It has as theoretical support the ecological aspects addressed by Marx throughout his works, from his doctoral thesis. In this it is evident that such author, who is referential in Social Work, had great concern with the environment. The fact that the third generation of human rights includes environmental preservation is also aligned with this aspect. Thus, due to the ethical principle of the intransigent defense of Human Rights, all Social Workers are deontologically committed to reviewing their knowledge and doing, perhaps, to promote new professional reconception, necessary, therefore, to meet the demands that arise in function of these Signs of time. It is an exploratory research whose result seeks to clarify a context. The methodology used dialectics, interviews, field research, bibliographic sources, documents and correlational studies